PENGARUH KEADILAN ORGANISASI DAN PEMBERDAYAAN TERHADAP KOMITMEN ORGANISASIONAL DI LSM BALADIKA BALI DPC DENPASAR - Kristiadi, Nyoman Sopian; Putra, Made Surya (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the effect of organizational justice, empowerment, towards commitment organizational. The research was conducted on caretakers Baladika Bali DPC Denpasar. Data analysis technique used is the technique of multiple linear regression analysis. Sample retrieval methods using saturation sampling with responses amounted 48 people. Data were collected using a questionnaire. The result showed that (1) organizational justice positive and significant effect on commitment organizational., (2) empowerment positive and significant effect on commitment organizational.
Keywords: organizational justice, empowerment, organizational commitment